2005
DOI: 10.1161/01.hyp.0000185648.48498.c1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Alteration of Adrenergic Responses in Small Femoral Arteries From Estrogen Receptor-β Knockout Mice

Abstract: Abstract-Estrogen receptor-␤ knockout mice become hypertensive as they age, and males have a higher blood pressure than females. We hypothesized that the absence of estrogen receptor-␤ may contribute to development of cardiovascular dysfunction by modification of adrenergic responsiveness in the peripheral vasculature. Small femoral arteries (internal diameter Ͻ200 m) were isolated from estrogen receptor-␤ knockout and wild-type mice and mounted on a wire myograph. Concentration-response curves to phenylephrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
6
18
0
Order By: Relevance
“…In the WT, these arteries similarly express ER-␣ and ER-␤, as detected and reported by our group recently, and ER-␤ is absent in these arteries from the ␤-ERKO mice (30). The choice of vasculature was also supported by studies in femoral arteries from rats in which dilatory responses to estrogens were sex specific and, at least in part, NO mediated (51).…”
supporting
confidence: 74%
“…In the WT, these arteries similarly express ER-␣ and ER-␤, as detected and reported by our group recently, and ER-␤ is absent in these arteries from the ␤-ERKO mice (30). The choice of vasculature was also supported by studies in femoral arteries from rats in which dilatory responses to estrogens were sex specific and, at least in part, NO mediated (51).…”
supporting
confidence: 74%
“…Previous studies (7,12,22,30,34) have identified both ER subtypes in vascular endothelium and smooth muscle in a wide range of blood vessels in different vascular beds and from different species. In this study, the dilatory actions of PPT, a selective ER␣ agonist, and genistein, a predominant ER␤ agonist, were enhanced compared with those to 17␤-E 2 , a mixed agonist, or to resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Each artery was mounted as an isometric preparation on stainless steel wires (diameter, 40 m) attached to a force transducer and a micrometer, respectively, as described previously (16,34). Commercially available software was used for calibrations and for data collection (Myodac, version 2.1, Danish Myo Technology).…”
Section: Patients Populationmentioning
confidence: 99%
“…As they age, male ER␤Ϫ/Ϫ mice develop hypertension due to abnormal adrenergic regulation of small artery tone (24). One of the consequences of hypertension is reduction in insulin-stimulated blood flow in SM (22).…”
Section: Discussionmentioning
confidence: 99%